Effects of high-intensity exercise training on physical fitness, quality of life and treatment outcomes after oesophagectomy for cancer of the gastro-oesophageal junction: PRESET pilot study. Issue 5 (28th August 2020) - Simonsen, C; Thorsen-Streit, S; Sundberg, A; Djurhuus, S S; Mortensen, C E; Qvortrup, C; Pedersen, B K; Svendsen, L B; Heer, P; Christensen, J F
Abstract: Background: Treatment for cancer of the gastro-oesophageal junction (GOJ) can result in considerable and persistent impairment of physical fitness and health-related quality of life (HRQoL). This controlled follow-up study investigated the feasibility and safety of postoperative exercise training. Methods: Patients with stage I–III GOJ cancer were allocated to 12 weeks of postoperative concurrent aerobic and resistance training (exercise group) or usual care (control group). Changes in cardiorespiratory fitness, muscle strength and HRQoL were evaluated. Adherence to adjuvant chemotherapy, hospitalizations and 1-year overall survival were recorded to assess safety. Results: Some 49 patients were studied. The exercise group attended a mean of 69 per cent of all prescribed sessions. After exercise, muscle strength and cardiorespiratory fitness were increased and returned to pretreatment levels. At 1-year follow-up, the exercise group had improved HRQoL (+13·5 points, 95 per cent c.i. 2·2 to 24·9), with no change in the control group (+3·7 points, −5·9 to 13·4), but there was no difference between the groups at this time point (+9·8 points, −5·1 to 24·8). Exercise was safe, with no differences in patients receiving adjuvant chemotherapy (14 of 16 versus 16 of 19; relative risk (RR) 1·04, 95 per cent c.i. 0·74 to 1·44), relative dose intensity of adjuvant chemotherapy (mean 57 versus 63 per cent; P = 0·479), hospitalization (7 of 19 versus 6 of 23; RR 1·41, 0·57 to 3·49) or 1-year overall survival (80 versus 79 per cent; P = 0·839) for exercise and usual care respectively. Conclusion: Exercise in the postoperative period is safe and may have the potential to improve physical fitness in patients with GOJ cancer. No differences in prognostic endpoints or HRQoL were observed. Registration number: NCT02722785 (https://www.clinicaltrials.gov ). Graphical Abstract: With concurrent aerobic exercise and resistance training twice a week during treatment, patients with cancer of the gastro-oesophageal junction can return cardiopulmonary fitness and muscle strength to pretreatment levels at completion of treatment. This can be done without affecting prognostic endpoints and with positive effects on health-related quality of life. Generally well tolerated and safe.